Investigation of pipe natural vibrations under different fixing conditions - Prykhodko, Nazar; Trubayev, Oleksandr; Larin, Andrew; Ponomarenko, Natalia (National Technical University "Kharkiv Polytechnic Institute", 2024)
The article investigates the modelling of boundary conditions for determining the natural frequencies of a cylindrical pipe using finite element models. Rod, shell, and solid-state models are used, and various variants of hinged, rigid, and rolling fixation conditions are investigated. The analysis of the natural vibration shapes shows the influence of the anchorage conditions on the shapes associated with the deformation of the pipe as a shell. The results obtained are important for the design and assessment of the service life of pipeline systems.
Keywords: cylindrical pipes; boundary conditions; natural frequencies; forms of oscillations; finite element method; modelling